2021
DOI: 10.1016/j.whi.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Affordable Care Act on Receipt of Women's Preventive Services in Community Health Centers in Medicaid Expansion and Nonexpansion States

Abstract: Background: The Affordable Care Act (ACA) increased health insurance coverage throughout the United States and improved care delivery for some services. We assess whether ACA implementation and Medicaid expansion were followed by greater receipt of recommended preventive services among women and girls in a large network of community health centers. Methods: Using electronic health record data from 354 community health centers in 14 states (10 expansion, 4 nonexpansion), we used generalized estimating equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…Enacted in 2010, the Affordable Care Act reduced financial barriers to routine adult vaccination and is associated with improved receipt of influenza vaccination among women. 30 Vaccination coverage in our study was consistently lower than vaccination coverage in a previous study that reported a flat trend in coverage from the 2010-2011 to 2016-2017 influenza season using survey data. 8 The discrepancy is likely the result of differences in methodologies: our estimates did not include vaccinations received outside health insurance plans, whereas survey data may overestimate true coverage because of issues such as social desirability bias and recall bias.…”
Section: Discussioncontrasting
confidence: 69%
“…Enacted in 2010, the Affordable Care Act reduced financial barriers to routine adult vaccination and is associated with improved receipt of influenza vaccination among women. 30 Vaccination coverage in our study was consistently lower than vaccination coverage in a previous study that reported a flat trend in coverage from the 2010-2011 to 2016-2017 influenza season using survey data. 8 The discrepancy is likely the result of differences in methodologies: our estimates did not include vaccinations received outside health insurance plans, whereas survey data may overestimate true coverage because of issues such as social desirability bias and recall bias.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition to this study, Zwetchkenbaum and Oh [ 46 ] found that the percentage of Medicaid enrollees who received dental care at Rhode Island CHCs also decreased following the ACA Medicaid expansion. However, other recent studies have shown that the Medicaid expansion created opportunities for CHCs to expand Medicaid coverage in CHC patient populations [ 17 ], improve access to preventive medical services [ 16 , 47 ], and expand patient revenue [ 18 ]. One explanation for our findings could be that expansion-state CHCs were infused with younger Medicaid-covered patients requiring less complex surgical services than non-expansion-state CHC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have assessed changes in cardiovascular preventive screenings following the ACA and Medicaid expansion. [7][8][9] Results from these studies showed improvement in glycemic screening but observed no change in blood pressure screening. Among patients with diabetes, there was a significant increase in screening for hemoglobin A1c in both expansion and non-expansion states, with a somewhat greater rise in expansion states.…”
Section: Diabetes and Hypertension Screeningmentioning
confidence: 99%